ANALISIS TINGKAT EFEKTIVITAS PENERAPAN SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK HIBURAN PADA PENDAPATAN ASLI CIREBON - Tatmimah, Itat; Muzayyanah, Muzayyanah; Indriyani, Rinni; Sari, Fitriya; Djajuli, M (2021)
This reseach aims to analyse the implementation of the entertainment tax-voting system in Cirebon. method using descriptive analysis. The subject of the Sub-Division head of indigenous revenue, the regional field staff of indigenous revenue, the budget agency, the Regional Representative Council of Cirebon. The result of data obtained that the voting mechanism is initiated from registration and logging, determination, depositing, accounting and reporting as well as billing tax collection conducted by the financial agency of the city of Cirebon in accordance with the prevailing regulations, as well as the procedure of objection and appeal, correction, cancellation, reduction of provisions, elimination or reduction of administrative sanctions and refund of overpaid entertainment tax .